Colombian Spanish design of the speech-in-noise discrimination test: Stage 1: Design of a contralateral and ipsilateral noise test and piloting in individuals with normal hearing - Buitrago Roa, Laura Melisa; Paez Pinilla, Amanda Teresa; Romero Niño, Eliana (Auditio, 2023)
Context: Difficulty understanding speech in noise is a common symptom of auditory processing disorders that impairs communication and affects different age groups. Objective: To design a first version of a speech-in-noise (SIN) discrimination test with contralateral and ipsilateral noise and pilot the test in the normal-hearing Colombian population. Method: Descriptive, exploratory study for test design and piloting. The pilot sample consisted of 10 men and 10 women aged 18-50 years without a neurotological history. For the statistical analysis, intelligibility of stimuli was measured and three interrelated categories were defined: Mode (contralateral or ipsilateral presentation of stimulus), Ear (left or right) and Noise (signal-noise ratio [SNR] of −5 dB and −10 dB). Results: The highest intelligibility was observed at −5 dB SNR, and stimuli were categorized as very easy; intelligibility at −10 dB SNR was 0.95 for words and 0.97 for sentences. The lowest intelligibility for words was 0.76 for the left ear, with ipsilateral noise at −10 dB SNR. Conclusions: According to our pilot test, the most suitable SNR is −10 dB. In the next stage of this test validation macroprocess, stimuli that were found to have very high or very low intelligibilities should be modified because they may hinder the interpretation of the test results.